Celsius Bloodhound : Automatizing searching and fetching records from library servers - De Giusti, Marisa Raquel (2007)
The Library Linkage Project (PrEBi) has as main objective to share the bibliographic acervus resident in ISTEC Institutions, in order to satisfy the demand of Researchers, Teachers and Students. To manage the bibliography requirements (journal articles, book chapters, congress proceedings, theses and patents) made by users, it's been developed the Celsius Software. Nowadays the main job of Celsius administrators is to lookup requests in ISTEC and non-ISTEC Institutions' catalogs by hand which takes many hours to check all until the resource is found. In order to perform this task more efficiently, it has been created in PrEBi the Celsius Bloodhound Project. This project, currently in analysis and design stage, intends to automatize this tedious job by searching and fetching records from library servers. Bloodhound's design is flexible enough to allow connections from almost any application and to connect to many different remote catalogues. Bloodhound will be able to interact transparently with many servers, taking advance of existing technologies and protocols, improving quality service in the search of resources in PrEBi and other Institutions as well.